The Role of Feedback in Improving Learning Outcomes of Islamic Religious Education Courses in Higher Education - Kurniawan. ZP, Iwan (Corolla International Conference, 2025)
This study aims to examine the role of feedback in improving student learning outcomes in Islamic Religious Education (IRE) courses at the higher education level. Feedback is widely recognized as an integral component of the teaching and learning process because it provides students with direction, correction, and encouragement that support both academic and personal development. Through feedback, students gain opportunities to reflect on their performance, identify areas for improvement, and reinforce their understanding of learning materials. This research employs a literature study approach by reviewing recent scholarly works, journal articles, and books published within the last five years that discuss the implementation of feedback in higher education, with specific attention to IRE courses. The findings of the review reveal that feedback, when delivered in a timely, specific, and constructive manner, positively influences student motivation, enhances engagement, and contributes significantly to knowledge retention. Furthermore, both formative and summative feedback strategies are shown to strengthen students’ conceptual understanding and support the achievement of intended learning outcomes. The study also emphasizes the crucial role of lecturers in designing effective feedback mechanisms, as the quality of feedback often determines the extent to which it can foster deeper learning. In conclusion, feedback functions not only as an evaluative instrument but also as a pedagogical strategy that can optimize learning and improve academic achievement in Islamic Religious Education courses in higher education.